PRODUKSI KEMANGI DI DESA CIARUTEUN ILIR, KECAMATAN CIBUNGBULANG, BOGOR - Widhiasih, Putri Larasati; Fariyanti, Anna; Tinaprilla, Netti (Forum Agribisnis, 2013)
Kemangi is one of indigenous plants that is widely consumed in West Java. It is planted by most farmers in Ciaruteun Ilir, which is the centre of its plantations in Bogor region. The main objective of this study was to analyse the production factors of kemangi in Ciaruteun Ilir. Thirty one respondents were needed in this study, using the method of Purposive Sampling. The production factors were analysed using Maximum Likelihood methods in Cobb-Douglas model. Based on the level of significance 5%, the results showed that seeds, Urea, labours, and land size significantly affected the production.